The Effectiveness of Stunting Prevention Programs in Indonesia : A Systematic Review - Pingkan Fristiwi; Sri Achadi Nugraheni; Apoina Kartini (Postgraduate, University of Mataram, 2023)
Stunting remains a major nutritional problem in developing countries, including Indonesia. This research aims to identify the effectiveness of stunting prevention programs in Indonesia. The research method employed in this study is a systematic review based on the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Article searches were conducted using five database; Scopus, ScienceDirect, ProQuest, Google Scholar, and Portal Garuda. The inclusion criteria for this research are articles published in the last 10 years, from 2014 to 2023, with a population in the Indonesian region. Based on the reviewed articles, it was found that the most effective stunting prevention measures include providing nutritional education to influential parties such as community health workers, mothers of toddler, and women of childbearing age or prospective mothers, interprofessional collaboration, and supplementary feeding. Trained community health workers are capable of reducing the stunting rates. Therefore the goverment should stengthen community health worker training to optimize stunting prevention through nutritional education.